Numerical Simulation of a Thermoelectric Generator for a Road Vehicle Application. Issue 3 (September 2016) - Vale, S; Heber, L; Coelho, P J; Silva, C M
Abstract: This paper presents a numerical model for a thermoelectric generator (TEG) on the tailpipe of commercial (3.5-ton) and heavy duty (40-ton) vehicles. The widths and lengths of the TEG for the two vehicles are 0.10 m × 0.15 m and 0.2 m × 0.15 m respectively. Exhaust gas is used as the heat source and cooling water is the heat sink. Both fluids flow in the same direction. The study examines the improvement in heat transfer from the exhaust gas side. A numerical model is developed that provides a choice between two different heat exchanger configurations with either plain fins or offset strip fins. The influence of fin height, length and spacing is analysed. According to the criteria used in this study, plain fins are a better choice, yielding a maximum electrical power of 107 W for the commercial vehicle and 480 W for the heavy duty vehicle.